2013
DOI: 10.5267/j.dsl.2013.08.002
|View full text |Cite
|
Sign up to set email alerts
|

A study to determine influential factors on data security

Abstract: During the past few years, there has been increasing interest in making online transaction. As people become more interested in using internet for their daily business activities such as regular communications, financial transactions, etc., there will be more concerns on security of available data. In fact, data security is the primary concern in today's online activities. This paper performs an empirical investigation to find important factors influencing data security in Municipality is city of Tehran, Iran.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…The results of this study are consistent with other findings (Beerli et al, 2004;San Martín & Herrero, 2012;Šebjan et al, 2014). Azad, et al (2014), for instance, performed an empirical investigation to find important factors influencing data security in Municipality of city of Tehran, Iran and determined that process approach and the acceptance were influencing the most on the performance of organizations. Zhu et al (2002) reported that IT-based services had direct impact on the SERVQUAL dimensions (Parasuraman et al, 1988) and an indirect impact on customer perceived service quality and customer satisfaction.…”
Section: Resultssupporting
confidence: 90%
“…The results of this study are consistent with other findings (Beerli et al, 2004;San Martín & Herrero, 2012;Šebjan et al, 2014). Azad, et al (2014), for instance, performed an empirical investigation to find important factors influencing data security in Municipality of city of Tehran, Iran and determined that process approach and the acceptance were influencing the most on the performance of organizations. Zhu et al (2002) reported that IT-based services had direct impact on the SERVQUAL dimensions (Parasuraman et al, 1988) and an indirect impact on customer perceived service quality and customer satisfaction.…”
Section: Resultssupporting
confidence: 90%
“…Azad et al (2013) presented an empirical investigation to determine important factors influencing DSSs and detected system, analysis and transaction as important issues. Azad et al (2014), in other survey, performed an empirical investigation to determine important factors influencing data security in Municipality is city of Tehran, Iran and determined six factors influencing feasibility study, organizational learning, management strategy, enterprise resource management, process approach and the acceptance.…”
Section: Introductionmentioning
confidence: 99%